2017
DOI: 10.1038/cddis.2017.206
|View full text |Cite
|
Sign up to set email alerts
|

Acidic pH is essential for maintaining mast cell secretory granule homeostasis

Abstract: It has been recognized for a long time that the secretory granules of mast cells are acidic, but the functional importance of maintaining an acidic pH in the mast cell granules is not fully understood. Here we addressed this issue by examining the effects of raising the pH of the mast cell secretory granules. Mast cells were incubated with bafilomycin A1, an inhibitor of the vacuolar-type ATPase proton pump. Supporting a role of vacuolar-type ATPase in mast cell granule acidification, bafilomycin A1 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…In cells, Baf‐A1 usually targets to the lysosomes for regulating cellular acidification (Yamamoto et al, ). The acidification of lysosomes revealed by the incubation with acridine orange was completely inhibited when cells were treated with 0.1–1 μM bafilomycin A1, then intracellular pH robust increased (Marrone et al, ; Pejler, Hu Frisk, Sjostrom, Paivandy, & Ohrvik, ; Yoshimori, Yamamoto, Moriyama, Futai, & Tashiro, ). Generally, cell acidification is essential for cell proliferation, autophagy, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In cells, Baf‐A1 usually targets to the lysosomes for regulating cellular acidification (Yamamoto et al, ). The acidification of lysosomes revealed by the incubation with acridine orange was completely inhibited when cells were treated with 0.1–1 μM bafilomycin A1, then intracellular pH robust increased (Marrone et al, ; Pejler, Hu Frisk, Sjostrom, Paivandy, & Ohrvik, ; Yoshimori, Yamamoto, Moriyama, Futai, & Tashiro, ). Generally, cell acidification is essential for cell proliferation, autophagy, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were confirmed ex vivo in human primary MCs ( 38 ). MC cytoplasm is notoriously packed with secretory granules, which display an acidic pH of 5.2 to 6.1, optimal for MC proteases ( 77 ). Experiments performed with bafilomycin A1, an inhibitor of vacuolar-type H + -ATPase (V-ATPase) sharing with CQ/HCQ the lysosomal tropism and the ability to increase pH in acidic compartments, showed that disruption of the acidic pH of MC secretory granules induced tryptase degradation ( 77 ).…”
Section: Mechanisms Of Cq/hcq-induced Immune Modulationmentioning
confidence: 99%
“…MC cytoplasm is notoriously packed with secretory granules, which display an acidic pH of 5.2 to 6.1, optimal for MC proteases ( 77 ). Experiments performed with bafilomycin A1, an inhibitor of vacuolar-type H + -ATPase (V-ATPase) sharing with CQ/HCQ the lysosomal tropism and the ability to increase pH in acidic compartments, showed that disruption of the acidic pH of MC secretory granules induced tryptase degradation ( 77 ). CQ/HCQ would be expected to reproduce such findings, whose main interest resides in the abrogation of the proinflammatory signals and effectors that are conveyed by intact MC proteases, such as tryptase, the best known in humans, which is involved in chronic allergic inflammation and tissue remodeling ( 77 79 ).…”
Section: Mechanisms Of Cq/hcq-induced Immune Modulationmentioning
confidence: 99%
“…Auch bei der Degranulation von Mastzellen spielt der pH-Wert eine entscheidende Rolle. Nur im sauren Milieu entwickelt der inflammatorische Cocktail seine volle Kraft [31].…”
Section: Merkeunclassified